Appraising the Conceptual and Lexical Retrieval in Persons with Fluent and Nonfluent Aphasia - Puttanna, Deepak; Theresa, Lorine Little; Swamy, Akshaya (Journal of Health and Allied Sciences NU, 2024)
Objective Conceptual knowledge refers to understanding and interpreting concepts and their relationships. Lexical knowledge is the knowledge that can be expressed through words. It entails meaning of words and their relationships. Word retrieval impairments are the most radical deficits that restrict communicative functions for individuals with aphasia. The current study aimed to compare the conceptual and linguistic impairments associated with fluent and nonfluent persons with aphasia (PWAs).Materials and Methods A total of 15 PWAs were recruited for the study, out of which, 8 were fluent aphasia and 7 were nonfluent aphasia. One picture-based conceptual task (picture comparison judgments) and one verb-based linguistic task (word comparison judgments) were used as the experimental paradigm.Results and Conclusion The findings of the study showed no significant difference in the performance of conceptual and lexical retrieval abilities in both fluent and nonfluent aphasia. The current study highlights the fact that both conceptual and lexical retrieval impairments prevail in both fluent and nonfluent aphasia.
Keywords: anomic; stroke survivors; aphasia; conceptual task